Japanese Migrations to Australia (Taylor & Francis, 2025)
This book stands as the first comprehensive English-language scholarly book dedicated to the dynamic and multifaceted aspects of Japanese migrations to Australia. By offering an extensive and up to-date analysis of migration trends, this book addresses a significant void in academic research. Structured into two parts, this book offers an in-depth exploration of various aspects of this migration. Firstly, by examining contemporary migration patterns including working holiday makers (WHMs), partnership-based migrants and Japanese–Australian youths, this book unsettles cultural essentialist and national exceptionalist narratives. Additionally, through investigations of Australian tourism, the role of Japanese restaurants in cultural exchange and the artistic expressions within the Nikkei Australian community, this book reveals the diverse contributions and interactions of Japanese communities in Australia and the bilateral influences of Japan. It also critically engages with the monolithic concept of ‘community’ through specific sectors and previously understudied groups including Japanese-Indigenous Australians and LGBTQ+ migrants, analysing how personal narratives align with or diverge from policy frameworks and offering new perspectives on identity and belonging in transnational contexts. Combining empirical research with theoretical analysis, this book is not only an academic resource but also a useful reference for policymakers. By offering new perspectives and policy recommendations, it is an invaluable tool for understanding and adapting to the evolving patterns of Japanese migrations to Australia, making a substantial contribution to the fields of Japanese, migration and Australian studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.